2018
DOI: 10.1016/j.stemcr.2018.01.026
|View full text |Cite|
|
Sign up to set email alerts
|

Calorie Restriction Governs Intestinal Epithelial Regeneration through Cell-Autonomous Regulation of mTORC1 in Reserve Stem Cells

Abstract: SummaryAging is a complex process associated with a decline in functionality of adult stem cells affecting tissue homeostasis and regeneration. Calorie restriction (CR) is the only experimental manipulation known to extend lifespan and reduce the incidence of age-related disorders across numerous species. These benefits are likely mediated, at least in part, through the preservation of stem cell function. Here, we show that CR enhances the regenerative capacity of the intestinal epithelium through preservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 34 publications
(65 reference statements)
2
64
0
Order By: Relevance
“…Although the exact phenotypes of ISCs of aging mice have yet to be robustly characterized, various studies have reported potential intervention strategies to restore function. Mihaylova et al (170) have found that fasting can promote ISC function by inducing fatty acid oxidation, whereas Yousefi et al (183) report that calorie restriction improves the regenerative capacity of the intestinal epithelium by mTORC1 inhibition in injury-resistant reserve ISCs. mTORC1 activity is critical for the transition of many SSC types to an active state but can significantly impair the function of these cells by promoting differentiation.…”
Section: Aging In the Mammalian Intestinementioning
confidence: 99%
“…Although the exact phenotypes of ISCs of aging mice have yet to be robustly characterized, various studies have reported potential intervention strategies to restore function. Mihaylova et al (170) have found that fasting can promote ISC function by inducing fatty acid oxidation, whereas Yousefi et al (183) report that calorie restriction improves the regenerative capacity of the intestinal epithelium by mTORC1 inhibition in injury-resistant reserve ISCs. mTORC1 activity is critical for the transition of many SSC types to an active state but can significantly impair the function of these cells by promoting differentiation.…”
Section: Aging In the Mammalian Intestinementioning
confidence: 99%
“…Albanes et al (1990) showed that 3 weeks of CR reduced DNA synthesis in the colon of young rats, which resulted in a decrease in the number of crypts and the total number of colonic mucosal cells dividing at any given time. In addition, 6-12 weeks of CR has been shown to have a significant impact on intestinal stem cell function in mice (Yilmaz et al, 2012;Yousefi et al, 2018), and we found that one-month of CR altered the expression of over 5000 genes (fold change >1.25) in intestinal mucosa from mice (Unnikrishnan et al, 2017). Thus, our data and previous data on the impact of CR on the GI-system indicate that the initial impact of CR occurs on the physiological status of the GI-system, suggesting that the subsequent changes in the microbiome occur because of these physiological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings that CR drives decreased mTORC1 levels, leading to improved regenerative potential of the ISCs, have also been validated in independent studies. 82,83 To study neurogenesis, adult mice (14 weeks old) were initiated onto a CR diet and maintained at 40% CR until they reached 6, 12, or 18 months of age. CR preserved neurogenesis levels in older mice compared to AL mice due to a maintenance of the number of neuroblasts (progenitor cells committed to becoming neurons) in the subventricular zone (SVZ) but did not protect against SVZ remodeling.…”
Section: Caloric Restrictionmentioning
confidence: 99%